Effect of substrate solarization on the production of sweet pepper seedlings (Research, Society and Development, 2022)
Soil and substrate solarization is an alternative as an efficient disinfestation method to eliminate pathogens, as it stimulates the development of antagonists, also acting in the control of pests and weeds, in addition to promoting plant growth. This work aimed to test the solarization of 4 substrates based on bovine manure, sheep manure, earthworm humus and commercial substrate, in 5 solarization times (0, 24, 48, 72 and 96h). The substrates were prepared by adding black earth and washed sand, and subjected to solarization on full sun days. After this procedure, the substrates were distributed in plastic trays suitable for the production of seedlings and pepper seeds were planted. The evaluation of the experiment was carried out when the seedlings presented about five definitive leaves. The indicators evaluated were: Plant Height (AP), Neck Diameter (DC), Number of Leaves (NF), Root Length (CR), % Leaf Dry Mass (MSF), % Stem Dry Mass (MSC) and % Dry Root Mass (MSR). The data obtained were submitted to analysis of variance and means compared by the Scott-Knott test and the Tukey test at 5% probability, using the statistical program Sisvar version 5.7. No seedlings with disease symptoms were found throughout the experiment. The commercial solarized substrate had significant differences between the indicators tested, showing greater efficiency in the solarization method. In the dry mass indicators, the tested substrates had significant results with solarization and can be used in family farming.